2013
DOI: 10.5121/ijcsit.2013.5306
|View full text |Cite
|
Sign up to set email alerts
|

Security Threats on Cloud Computing Vulnerabilities

Abstract: Clouds provide a powerful computingplatformthatenablesindividuals and organizationsto performvariety levelsoftasks such as:use of online storage space,adoption of business applications,development ofcustomizedcomputersoftware,andcreation of a“realistic” network environment.Inpreviousyears,the number of people using cloud serviceshasdramatically increased and lots of datahasbeenstoredin cloud computing environments.In the meantime, data breaches to cloud servicesarealsoincreasingevery yeardue tohackerswhoarealw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 14 publications
0
58
0
1
Order By: Relevance
“…AlertLogic conducted a research on the state of Cloud security from its 2,200 customers. Their research found that in 2014, 44% of the customers experienced a brute force attack compared to 30% of customers a year earlier [41]. There was an equal percentage of vulnerability scans (44%) which have also increased from 27% a year earlier [41].…”
Section: Confidentiality and Privacymentioning
confidence: 93%
See 2 more Smart Citations
“…AlertLogic conducted a research on the state of Cloud security from its 2,200 customers. Their research found that in 2014, 44% of the customers experienced a brute force attack compared to 30% of customers a year earlier [41]. There was an equal percentage of vulnerability scans (44%) which have also increased from 27% a year earlier [41].…”
Section: Confidentiality and Privacymentioning
confidence: 93%
“…This helps put customers at ease since they have a clear understanding of how their personal data will be used. The major threat to data confidentiality and privacy is from the employees of the Cloud service providers who have Table 10 Key Findings Key Findings References Cloud service providers face a plethora of security issues and need to implement various security measures [12,13,41] Different data security measures need to be put in place for the various phases of the data life cycle, specially to ensure data confidentiality and privacy [36,57] Cloud service providers should disclose exactly what personal data will be collected and what that data will be used for, thereby maintaining privacy and confidentiality [36] Data should be properly encrypted so that it cannot be accessed or misused by the employees of service provider [38,39] Malicious attacks from hackers need to be prevented at every stage of the data life cycle so that there is no breach of data confidentiality [40,43] Cloud services have to comply with the country's legal rules, which includes disclosing customer data to the law enforcement agencies if needed [13,37] access to customer data. In order to protect the data from being misused by the employees, it is necessary to have a good data encryption, which makes it difficult for employees to access the data itself, thereby ensuring privacy and data confidentiality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have discussed about In [4], Chou has discussed about many security threats and attacks and categorized them in two broad terms that are malware injection attacks and wrapping attacks. The malware injection attack covers cross-site scripting attacks and SQL injection attacks.…”
Section: Literature Surveymentioning
confidence: 99%
“…Some hackers have moved from gambling with servers and operating systems to exploiting computer browsers and email level of users (Chou, T. 2013). …”
Section: Literature Reviewmentioning
confidence: 99%